Twin pregnancy with metastatic complete molar pregnancy and coexisting live fetus - Odedra, Devang (Radiol Case Rep, 2019)
We present a case of a 34-year old G1P0 female with twin-gestation and positive prenatal screening. Initial ultrasounds demonstrated a normal live fetus with an indeterminate but persistent placental lesion. The patient presented at 23 weeks of gestational age with vaginal bleeding. On examination, a 2 cm vaginal lesion was identified. Further cross-sectional imaging demonstrated a normal appearing fetus with a mixed solid and cystic placental lesion as well as an additional lesion in the vagina. Metastatic workup revealed diffuse pulmonary metastases. Intravascular embolization was carried out to minimize the bleeding from the vaginal lesion, followed by the delivery of the fetus with an urgent Caesarean section and treatment with chemotherapy. Pathology and genetics testing confirmed diagnosis of a complete molar pregnancy with a coexisting live fetus. This case highlights the importance of any unexpected findings within the placenta or the uterus in a pregnant patient. The radiologist should maintain a high index of suspicion for gestational trophoblastic disease in such cases, communicate clearly with the clinical team and suggest appropriate additional imaging.